Inherent Role of Water in Damage Tolerance of the Prismatic Mineral–Organic Biocomposite in the Shell of Pinna Nobilis. (30th March 2016) - Bayerlein, Bernd; Bertinetti, Luca; Bar‐On, Benny; Blumtritt, Horst; Fratzl, Peter; Zlotnikov, Igor
Abstract : The combination of high stiffness, strength, and toughness of many biological tissues is achieved through complex 3D arrangement of hard and soft components. While the hard building blocks are associated with the general stiffness of these biocomposite structures, the soft organic constituents provide the necessary flexibility and toughness and are susceptible to moisture uptake. Because many biological materials reside in humid environments, water is an inherent component of their microstructure. Hence, many studies have emphasized the effect of moisture content on mechanical performance of these materials. High toughness is indeed reported in materials, such as bone, teeth, mollusk shells, and glass sponges, when measured in high relative humidities, nevertheless, not much is known about the exact mechanisms that are responsible for this phenomenon. In the present work, newly developed environmentally controlled nanomechanical characterization techniques are employed to probe the prismatic layer in the shell of Pinna nobilis consisting of hard calcitic blocks surrounded by 1 μm thick organic matrix. Using spatially resolved mechanical data, it is demonstrated that water not only strongly affects the mechanical properties of the biocomposite tissue and its constituents but also is an integral part of explicit intrinsic and extrinsic toughening mechanisms revealed in this study. Abstract : Mechanical performance of the prismatic calcite‐organic biocomposite structure in the shell of the bivalve mollusc Pinna nobilis is strongly dependent on high moisture content inherent to its marine habitat. Water is not only an integral structural component but also plays a key role in various toughening mechanisms responsible for the high damage tolerance of the shell.